Gender identity in cross-border mobility: personal and family aspects - Jiménez Blanco, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Gender self-determination has a personal aspect and a family aspect. The first has implications for the identification of the person and, to this end, Law 4/2023 has introduced a double system that discriminates based on nationality, unjustifiably excluding foreign persons from registration rectification. Along with this, there is no provision on international judicial jurisdiction or on applicable law which, by analogy with the state and the name, should be the national law. The family aspect measures the impact of gender self-determination on marriage capacity and the establishment of parenthood, introducing correctives to the laws applicable to these issues.